Literacy on the move: a journal for the journey - Curtis, Laurie J. (My University, 2013)
Travel provides students with multiple opportunities to learn about people, places, and the world around them. At times, students are given opportunities to travel causing them to be absent from the classroom. This manuscript provides a practical model to engage students in learning while on the journey. Students are asked to share and expand upon their experiences through narrative writing, creative illustrations, and the reading of print resources (menus, maps, brochures, etc). Authentic reading and writing experiences help students connect curriculum within the classroom to the contexts in which they see literacy used outside the classroom. In this project students return to their classroom to share their new learning while teachers can use their writing as a form of authentic assessment. Connections to the Common Core State Standards are provided to demonstrate the curricular content of this project.
Keywords: Assessment; Family literacy; Writing; Motivation/engagement; Instructional strategies